Success Strategy for the Trans Jogja to Leverage its Services post COVID-19 Pandemic using Kano Model - Emaputra, Andrean; Nagara, Achmad Odyk Akbar; Mawadati, Argaditia; Sulistyaningsih, Eka (JDM (Jurnal Dinamika Manajemen), 2023)
Trans Jogja is the public bus Special Region of Yogyakarta Local Government has developed. The number of bus users declined during the COVID-19 pandemic because of mobility restrictions and online activities like schools and offices. This study aims to identify what quality attributes Trans Jogja should have to leverage its customer satisfaction and the customer number using the services. This study used the Kano model. The respondent number of respondents is 100 people. Eighty percent of the respondents have used the Trans Jogja more than twice. There are thirteen attractive quality attributes. For example, the bus provides free Wi-Fi internet access and an excellent passenger seat. There are four one-dimensional quality attributes Trans Jogja should consider. For instance, the bus has become convenient mass transportation. The only must-be quality attribute is that Trans Jogja guarantees safety. It is expected that the higher customer satisfaction, the higher the number of customers using the bus services..